Will an organic label always increase food consumption? It depends on food type and consumer differences in health locus of control. (January 2018) - Lee, Hsiao-Ching; Chang, Chun-Tuan; Cheng, Zhao-Hong; Chen, Yen-Ting
Highlights: We examine whether the organic label (OL) increases food consumption. Food type (FT) and health locus-of-control (HLOC) are two moderators. The perceived healthiness mediates the effects of OL and FT on consumption. To externals, an organic label increases (reduces) vice (virtue) food intake. To internals, it reduces vice food intake but does not impact virtue food intake. Abstract: Food companies that choose to differentiate themselves by marketing their products as organic assume that the organic label tells consumers that the food is healthy. This research examines whether the organic label on a food product always increases consumer consumption of that product. Two moderators are considered: food type (virtue vs. vice) and consumer differences in health locus-of-control (HLOC) (externals vs. internals). Study 1 indicates that an organic label enhances consumers' intention to consume vice food, but eliminates their intention to consume virtue food. Study 2 suggests that the joint effect of the organic label and food type differs for externals and internals. The results for externals are consistent with those in Study 1: an organic label increases vice food intake but reduces virtue food intake. Different results are observed for the food intake of people with an internal HLOC: an organic label actually eliminates vice food intake but has no effect on the intake of virtue food. These results show that an organic label can either increase or decrease food consumption depending on food type and HLOC, simultaneously. The findings provide managerial implications for food companies and public policy makers.